Alam Semesta dalam Persepektif Al-Qur’an dan Hadits - sada, Heru Juabdin (Universitas Islam Negeri Raden Intan Lampung, 2016)
Al-Qur'an is a book of guidance. Allah revealed her to explain to the people the things that can not be understood by human reason, as the essence of faith and rituals of the foundations of ethical and legal useful to regulate the social interaction between human beings. The Qur'an also speaks of the universe, which includes everything that is in the heavens and the earth. Even more than a thousand verses that speak of it to prove the power, knowledge, and infinite wisdom of the creator who is capable of creating eliminate and restore the original natural kebentuk keep this feast. Her light will continue to burn for millions of years without outages, this is a result of the interaction of atoms in the star's known the term